PENGARUH PERPUTARAN PIUTANG, PERPUTARAN KAS DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN TEKSTIL DAN GARMENT YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Ika Wahyuni; Lusiana Tulhusnah (Growth, 2020)
This study aims (1) to determine the effect of accounts receivable turnover, cash turnover, and sales growth which have a partial effect on profitability (2) to determine the effect of accounts receivable turnover, cash turnover, and sales growth simultaneously on profitability (3) to determine between turnover. accounts receivable, cash turnover, and sales growth which have the most dominant influence on profitability. The method used in this research is quantitative method. The result of this research is multiple linear regression equation Y = 0.025 - 0.003 X1 + 0.000 X2 + 0.225 X3 + e. Accounts receivable turnover partially has no significant effect with a value of -0.680, of -2.028, cash turnover has no significant effect with a value of -1.559, of -2.028, sales growth has a significant positive effect with a value of 3.368, amounting to 2.028. Simultaneously, accounts receivable turnover, cash turnover and sales growth have an effect on profitability with a value of 4.744, amounting to 2.87. The variable with the most dominant influence in this study is sales growth with a value of 3.368.